Peoples versus states: minorities at risk in the new century - Gurr, Ted Robert (United States Institute of Peace Press, 2000)
The ethnic basis of political action in the 1980s and 1990s. Turks in Germany: from guest workers to ethnoclass / Ted Robert Gurr -- Long war, short peace: the rise and decline of ethnopolitical conflict at the end of the Cold War. The "Russian minority" in Ukraine / Marion Recktenwald -- The etiology of ethnopolitical conflict. Indigenous peoples of Amazonian Ecuador: a little help from their friends / Pamela L. Burke. Afro-Brazilians: poverty without protest / Pamela L. Burke and Ted Robert Gurr -- Incentives for ethnopolitical conflict: world patterns of discrimination and repression in the 1990s. Chinese in Malaysia: balancing communal inequalities / Deepa Khosla. The Copts in Egypt: a Christian minority in an Islamic society / Jonathan Fox. The Roma in the postcommunist era / Jonathan Fox and Betty Brown -- Democratic governance and strategies of accommodation in plural societies. The indigenous peoples of Bolivia: mobilization and empowerment in the 1990s / Ted Robert Gurr and Pamela L. Burke. Hungarians in Slovakia: the last stage of communism is nationalism / Be(c)Łta Kov(c)Łcs N(c)Łs. Burundi in the 1990s: from democratization to communal war / Michael Dravis -- The challenge of resolving ethnonational conflicts. Tibetans: dim prospects for settling a protracted ethnonational conflict / Deepa Khosla. The Gagauz of Moldova: settling an ethnonational rebellion / Ted Robert Gurr and Michael L. Haxton -- Assessing risks of future ethnic wars / Ted Robert Gurr and Monty G. Marshall. Political rivalries and communal vengeance in Kenya / Anne Pitsch. Muslims in India and the rise of Hindu communalism / Mizan Khan with Ted Robert Gurr -- Conclusions: managing conflict in heterogeneous societies -- Appendixes. Classification of countries by region type in the late 1990s. The analytic basis of risk assessment / Ted Robert Gurr and Monty G. Marshall. Additional groups for the Minorities at Risk Study / Deep Khosla. Background characteistics of ethnopolitical groups and risk of rebellion / Anne Pitsch. Estimating 1990s populations of groups in the Minorities at Risk Study / Ted Robert Gurr and Marion Rechtenwald